Synthesis and characterization of superhydrophobic-superoleophilic surface - Mahadik, Satish A.; Pedraza, Fernado D.; Relekar, Brahmanand P.; Parale, Vinayak. G.; Lohar, Gaurav M.; Thorat, Sagar S. (Journal of Sol-Gel Science and Technology, 2016)
The binary superhydrophobic-superhydrophilic surface has been successfully achieved by a combination of nanoscale texture roughness on micro-textured cotton thread network by layer-by-layer deposition method through the single-step sol-gel route. Furthermore, microstructures with improved wettability were produced, in which silica nanotextures were grown without modifying the chemical method to form superoleophilic and superhydrophobic networks. A superoleophilic surface (oil contact angle 0A degrees) and a superhydrophobic coated cotton fabric with surface free energy of gamma (total) = 13. 23 +/- A 0.37 mJ m(-2) (water contact angle of 167 +/- A 1A degrees and a small sliding angle of 4 +/- A 1A degrees) were successfully obtained. The results were exemplified here by the creation of immiscible oils separation membranes, and the innumerable applications of this technology also include self-cleaning fabrics, antistaining fabrics, water purification, and antiwetting fabrics for military applications.
Keywords: contact angle; Layer-by-layer deposition method; sol-gel processing; Superhydrophobic-superoleophilic surface